2019
DOI: 10.1111/jsbm.12388
|View full text |Cite
|
Sign up to set email alerts
|

Small Firms in Regional Clusters: Local Networks and Internationalization in the Southern Hemisphere

Abstract: This paper reports on a three‐country comparative study examining the internationalization of family winemakers in distinct regional wine clusters of Argentina, Chile, and New Zealand. In‐depth interviews were conducted with owner–operators, to understand the drivers and barriers to internationalization of their businesses. Key findings reveal that while size and age are not determinants of the ability or propensity to export wine, the existence of an independent industry body has a positive impact and greatly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
107
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 140 publications
3
107
0
2
Order By: Relevance
“…However, research on mediators/moderators has only recently begun investigating the mediators and moderators between antecedents and internationalization outcomes (Felzensztein et al . 2019; Qian et al . 2018; Nakos et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, research on mediators/moderators has only recently begun investigating the mediators and moderators between antecedents and internationalization outcomes (Felzensztein et al . 2019; Qian et al . 2018; Nakos et al .…”
Section: Introductionmentioning
confidence: 99%
“…1 First, coopetition was expected to have a quadratic relationship with financial performance (Crick and Crick 2021; Luo, Rindfleisch, and Tse 2007). Second, export intensity and export geographical scope were anticipated to positively moderate this nonlinear (inverted U-shaped) association (Chetty and Wilson 2003; Felzensztein, Deans, and Dana 2019). Third, the outcome variable (namely, financial performance) was controlled for firm size, firm age, and competitive intensity, as additional factors that might explain its variance (Crick and Crick 2020; Leonidou et al 2013; Vorhies, Orr, and Bush 2011).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…They argued that because of the economic and health-related shocks that the novel coronavirus has caused, various firms (small and large) have found that it is beneficial to work with rivals to access vital equipment and information, as well as sharing certain risks and costs that might make the difference between surviving and failing in these volatile circumstances. Although motives for engaging in coopetition activities vary, the underlying aim is to obtain mutually beneficial outcomes rather than employing an individualistic business model (linking with Bengtsson and Kock 2014; Felzensztein, Deans, and Dana 2019; Hannah and Eisenhardt 2018). Nonetheless, the management of coopetition relationships is likely to be complex because of competitive forces that might limit the performance outcomes of these interfirm partnerships (Mattsson and Tidstrom 2015; Park, Srivastava, and Gnyawali 2014).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations